Penggunaan Gadget dalam Mendukung Proses Pembelajaran Pada Anak Usia Dini di RA Mathlaul Ulum Jayasari - Nuri Andiani Putri; Aang Andi Kuswani (Edu Happiness: Jurnal Ilmiah Perkembangan Anak Usia Dini, 2025)
The main role of educational technology is to help improve overall efficiency in the teaching and learning process. The application of educational technology in education should make the educational process in general, and teaching and learning in particular, more efficient, effective, and provide positive added value. However, not all teachers can maximize and properly utilize technology. They do not fully understand how to access information via the internet, and facilities such as gadgets are often only used to play videos, even though the use of these media can be beneficial by providing various types of content and giving teachers insights and inspiration for innovative activities. Therefore, the purpose of this research is to examine how the use of gadgets supports the learning process for early childhood at RA Mathlaul Ulum Jayasari. This research is a qualitative study with a phenomenological approach using data collection techniques such as interviews, observations, open and directed discussions, and documentation studies involving the principal, teachers, and students at RA Mathlaul Ulum Jayasari to describe the use of gadgets in supporting the learning process for early childhood at RA Mathlaul Ulum Jayasari. The results of the study